Pengukuran Kinerja Mesin 3 dan Analisis FMEA pada Proses Produksi Resin di PT. XYZ - Atikah Mariah Ulfa; Septian Rahmat Adnan (Universitas Teuku Umar, 2021)
XYZ Inc. is one of manufacturing companies that produce eco friendly polymer/resin. Five production machines were used to do some production process such as mixing and extracting. Production machine number three often suffered trouble that caused production stop. the purpose of this research is to calculate performace of production machine number three using Overall Equipment Effectiveness (OEE) and analyze the elements that caused failure of production machine number three using Failure Mode and Effect Analysis (FMEA). The data that used in this research was January to December 2019. The result showed that average OEE value is 70,49%, the highest RPN value is 448 on heating process and critical component of production machine number three was heater.